Workplace Safety Interventions for Commercial Fishermen of the Gulf. Issue 2 (2nd April 2016) - Levin, Jeffrey L.; Gilmore, Karen; Wickman, Amanda; Shepherd, Sara; Shipp, Eva; Nonnenmann, Matthew; Carruth, Ann
ABSTRACT: Commercial fishing continues to have one of the highest rates of occupational fatalities compared with other work sectors in the United States. Attitudes/beliefs among Vietnamese shrimp fishermen of the Gulf of Mexico may influence behaviors that are risk factors for fatal and nonfatal injuries. The study employs a community trial with quasi-experimental pretest/posttest intervention design. An advisory group made up of key stakeholders including representatives from the US Coast Guard was assembled. A survey was designed using the Theory of Planned Behavior as the theoretical framework. Three community groups at port sites along the Texas/Louisiana Gulf Coasts were identified. Focus groups were convened at each site to select priority areas for risk intervention using training and awareness measures. Initial and follow-up surveys were administered pre-/post-interventions for each of the three community groups (2008, n = 217 completed surveys; 2012, n = 206 completed surveys). The follow-up survey was condensed and "intent to act" questions were added for the priority concerns identified (noise-induced hearing loss, machinery/winches, and fatigue). Statistically significant changes ( P ranging from .000 to .042) were observed in selective attitude/belief responses for hearing/noise and fatigue. Intent to action or to adopt the intervention was high among all three groups of shrimp fishermen (hearing conservation, 82.4%; machinery/winch safety, 94.6%; fatigue awareness, 95.3%). Simple, yet culturally appropriate training and awareness measures in the form of visual and written safety messages favorably influence attitudes, beliefs, and behavioral intent related to priority risk factors identified by Vietnamese commercial shrimp fishermen along the Texas and Louisiana Gulf Coasts.